MORALITY AS A PSYCHOLOGICAL CATEGORY AND CHARACTERISTIC OF A PERSON (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This аrticle deаls with the notion of morality as a core psychological category and a fundamental characteristic of human personality. The study examines how moral values, norms, and principles are internalized within an individual’s psychological structure and how they manifest in behavior, decision-making, and interpersonal interactions. Theoretical perspectives from developmental psychology, moral philosophy, and social psychology are integrated to understand the formation and functioning of morality throughout different life stages. Furthermore, the study aims to identify the psychological mechanisms that influence moral development, such as empathy, conscience, and moral reasoning, as well as the role of environmental factors like culture, family, and education.